DINAMIKA PERUBAHAN PETA BATAS DAS MALUKA PROVINSI KALIMANTAN SELATAN - Rudianto Rudianto; Syarifuddin Kadir; Kissinger Kissinger; Mahrus Aryadi (Lambung Mangkurat University-Indonesia, 2020)
A study on the dynamics of the Change Dynamics of the Maluka Watershed Boundary Map in South Kalimantan Province, which aims to analyze the Maluka Watershed Boundary is a large-scale approach, analyzing the dynamics of changes in some watershed characteristics (morphological and morphometric aspects) and conducting a policy direction towards the Compilation of the Maluka Watershed Boundary Watershed. The results of the Maluka watershed boundary scale of 1:50.000 there are changes and improvements in watershed boundaries in the downstream watershed due to river drainage, dredging, river displacement caused by human activities, new watersheds formed and SRTM level 30 x 30 m resolution, line repair and correction coastal and river networks and optical remote sensing. Morphometric and morphologic characteristics of Watersheds Significant changes in watershed area and administration area (reduced by 4.678 Ha or 5,3%). Other properties did not change significantly (Hydrologic DAS: 2 sub-watersheds, namely the Bati-Bati sub-watershed and Banyuhirang sub-watersheds), (Watershed shape: elongated (Rc <0,5)), (Slope class: flat 90,24%, steep and rather steep 2,14%), (Altitude/Elevation) Watershed: 2 masl to 50 masl 81,71%, above 300 masl 4,37%), (Watershed orientation: heading east to west in a straight direction, middle watershed symmetrical ballooning), (flow density, index value: 1,09 medium category) and (DAS flow pattern: Dendritic). Policy recommendations are suggested to synchronize the implementation of UU No. 23 Tahun 2014 and UU No. 37 Tahun 2014 in terms of carrying out the mandate of PP. 37 Tahun 2012, namely the implementation of the management of watershed management in the context of conservation of land, water in the ecosystem/watershed unit by giving the mandate to assist the task of sub-affairs management of watershed management from the provincial government to the district / city government.